2021
DOI: 10.1002/nop2.1079
|View full text |Cite
|
Sign up to set email alerts
|

Research ability and research motivation of postgraduate nursing students in traditional Chinese medicine colleges

Abstract: The cultivation of nursing research ability has been recognized as a significant challenge worldwide (Ballesteros-Rodriguez et al., 2020;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 75 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The same study found that in order to encourage students to engage in independent research, they need targeted training and capacity-building to familiarize them with the necessary research skills. 7 Other studies have identified institutional and peer factors such as rating of the research output through the h-index and its positive impact upon a higher probability of research accepted for publications. 14 A study from Oman also identified that a dedicated research training program can more than double postgraduate health professionals’ research outputs such as publications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study found that in order to encourage students to engage in independent research, they need targeted training and capacity-building to familiarize them with the necessary research skills. 7 Other studies have identified institutional and peer factors such as rating of the research output through the h-index and its positive impact upon a higher probability of research accepted for publications. 14 A study from Oman also identified that a dedicated research training program can more than double postgraduate health professionals’ research outputs such as publications.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Therefore, preparing a future cadre of clinical researchers and increasing institutional publications require incorporating the research component into medical training programs at both undergraduate and postgraduate levels. 7 , 8…”
Section: Introductionmentioning
confidence: 99%
“…The independent learning abilities of the two groups were evaluated using an independent 30-item learning capacity rating scale developed by [32]. Items were scored on a ve-point Likert scale (1 = completely inconsistent; 5 = completely consistent).…”
Section: Measurementmentioning
confidence: 99%